Pleurodema nebulosum (Mendoza Four-eyed Frog). Endoparasites - Castillo, Gabriel Natalio (2023)
Pleurodema nebulosum occurs in several provinces of Argentina in the dry Chaco and Monte ecoregions (Vaira et al. 2012. Cuad. Herpetol. 26:131–159). We examined the body cavity of 38 adult P. nebulosum (45 mm mean SVL) collected over three years (2017–2019) in Presidente Sarmiento Provincial Park in San Juan Province, Argentina and deposited in the herpetology collection of the Universidad Nacional de San Juan as (UNSJ 4076-4096). The body cavity was opened by a mid-ventral incision and the interior was searched for helminths utilizing a dissecting microscope. Ten cestodes were found in the stomachs of two individuals. The cestodes were placed in hot distilled water to relax them and subsequently fixed in 10% formalin. They were then stained with hydrochloric carmine, dehydrated, and mounted on slides containing Canada balsam. They were examined with a light microscope and identified as Cylindrotaenia sp., similar to C. americana (Cyclophillidea: Nematotaenidae) (Jewell 1916. J. Parasitol. 2:181–192). The specimens were deposited in the parasitological collection of the Department of Biology, National University of San Juan (UNSJPar 282). They exhibited the following characteristics: paruterine capsules not surrounded by membranes and paruterine organs surrounded by growing cells. Infection prevalence was 5.26%; mean intensity was 5 ± 1.41 SD, range: 4–6 and mean abundance was 0.26. In Argentina, there is only one report of Cylindrotaenia sp. as a parasite; parasitizing Rhinella major in Formosa province, Argentina (Hamann and González 2015. Acta Herpetol. 10:9–101). In this note, the distribution of Cylindrotaenia sp. is expanded and P. nebulosum is a new host record for C. cf. americana.